Added Sugar and Oral Health: A Position Paper of the Brazilian Academy of Dentistry - Feldens, Carlos Alberto; Pinheiro, Liana L.; Cury, Jaime A.; Mendonça, Flávia; Groisman, Mario; Costa, Rafael A. H.; Pereira, Henrique C.; Vieira, Alexandre R. (Frontiers in Oral Health, 2022)
Excessive sugar consumption is the main cause of dental caries. Dental caries is highly prevalent and negatively impacts the quality of life at all stages. Furthermore, dental caries is associated with other noncommunicable conditions and diseases, such as obesity, diabetes, and cardiovascular diseases. The aim of this paper is to propose recommendations at the individual and population levels for health professionals, families, educators, stakeholders, and public officials to reduce the burden of dental caries and other noncommunicable diseases that are caused by the excessive sugar intake. A systematic search was performed in PubMed and Cochrane databases was performed to investigate the effectiveness of strategies and policies aiming to reduce sugar consumption as well as the impact of different patterns of sugar consumption on the occurrence of dental caries. Reference list of the identified papers and practice guidelines were manually reviewed as well. Based on the best evidence available, the Brazilian Academy of Dentistry recommends not to offer sugars to children younger than 2 years of age, and to limit total sugar consumption to less than 25 grams per day after 2 years of age. Furthermore, families should be informed to limit sugar exposure, sugar-free areas should be available, content of food labels and advertisement should be regulated, taxation of products with sugar should be introduced, and reformulation of foods and drinks to reduce concentrations of sugars should be considered.